Thermometry of flow fields using a two-color ratiometric PLIF technique - Heronemus, Seth M. (Kansas State University, 2018)
In this thesis, a two-color ratiometric planar laser-induced fluorescence (PLIF) technique for the measurement of temperature fields in liquids is described. The method uses the temperature sensitive rhodamine B and temperature insensitive rhodamine 110 fluorescent dyes. The ratio of the fluorescent emission intensity of these two dyes is inversely proportional to temperature and is independent of laser intensity variation in the flow field. Because the emission spectra of these two dyes overlap, a correction was developed to disentangle the two signals. In addition, the absorption spectra of rhodamine B and rhodamine 110 and emission spectrum of rhodamine 110 overlap, leading to the self-attenuation of the rhodamine 110 signal by the dye solution. A correction with respect to path length was developed for self-attenuation. This thesis presents the calibration process for a PLIF thermometry system and visualization of temperature gradients in a glass water tank with motion induced by large temperature gradients. A step-by-step procedure of the final calibration process is also presented.
Keywords: Fluorescence; Rhodamine; Temperature measurement; Planar laser-induced fluorescence